The Correlations of Knowledge, Attitude and Practice with Compliance in Treatment of Pulmonary Tuberculosis Patients in Puskesmas Cakranegara - Auliana Puji Lestari; Prima Belia Fathana; Wahyu Sulistya Affarah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Patient compliance refers to the suitability of behavior against treatment recommendations include timing, dose and frequency of treatment. Compliance to tuberculosis treatment was actually very complex and dynamic with various factors that interacted each other, and therefore it will influence on patientÃ¢â¬â¢s behavior decision. Patient who has a good compliance will increase success to his recovery. This study was carried out to determine the correlation between tuberculosis patient behavior which consists of the domain of knowledge, attitudes and practices with compliance to taking anti-tuberculosis drugs at the Puskesmas Cakranegara commencing on July to November 2020. This research was an observational analytic study using a cross sectional method. Population sample was patients who diagnosed with pulmonary tuberculosis which undergoing category 1 treatment at Puskesmas Cakranegara. The data used in the study was primary data established from interviewing patients using a questionnaire on selected Pulmonary TB patients including respondents who eligible as the inclusion and exclusion criteria. The number of samples in this study were 30 infected-people. The data obtained were analyzed using the Spearman correlation test.ÃÂ The correlation test of the study showed that there was no significant correlation between variable of knowledge and medication compliance (p = 0.079, r = 0.325).ÃÂ However, the attitude variables had a significant correlation with medication compliance (p = 0.000, r = 0.715).ÃÂ Similarly, the practices variable has a significant correlation to the medication compliance (p = 0.000, r = 0.656). This study found that there was no significant correlation between knowledge and compliance taking anti-tuberculosis drugs. However, it was found that there was a significant correlation between attitudes and practices with compliance to taking anti-tuberculosis drugs.